Numerical Simulation of Residual Stresses and Distortions in Butt Weld in Simulation Programme Sysweld - Konar, Radoslav; Mician, Milos (Communications - Scientific letters of the University of Zilina, 2012)
The article describes the theoretical knowledge of the residual stresses induced during welding in butt welded joint and the possibilities of their simulations in a simulation programme SYSWELD. In conclusion are compared experimental and simulated results.